New Insights into the Role of Macrophages in Adipose Tissue Inflammation and Fatty Liver Disease: Modulation by Endogenous Omega-3 Fatty Acid-Derived Lipid Mediators - Clària, Joan; González-Périz, Ana; López-Vicario, Cristina; Rius, Bibiana; Titos, Esther (Frontiers in Immunology, 2011)
Obesity is causally linked to a chronic state of “low-grade” inflammation in adipose tissue. Prolonged, unremitting inflammation in this tissue has a direct impact on insulin-sensitive tissues (i.e. liver) and its timely resolution is a critical step toward reducing the prevalence of related co-morbidities such as insulin resistance and non-alcoholic fatty liver disease. This article describes the current state-of-the-art knowledge and novel insights into the role of macrophages in adipose tissue inflammation, with special emphasis on the progressive changes in macrophage polarization observed over the course of obesity. In addition, this article extends the discussion to the contribution of Kupffer cells, the liver resident macrophages, to metabolic liver disease. Special attention is given to the modulation of macrophage responses by omega-3-PUFAs, and more importantly by resolvins, which are potent anti-inflammatory and pro-resolving autacoids generated from docosahexaenoic and eicosapentaenoic acids. In fact, resolvins have been shown to work as endogenous “stop signals” in inflamed adipose tissue and to return this tissue to homeostasis by inducing a phenotypic switch in macrophage polarization toward a pro-resolving phenotype. Collectively, this article offers new views on the role of macrophages in metabolic disease and their modulation by endogenously-generated omega-3-PUFA-derived lipid mediators.